THE EFFECT OF INFLATION, BI RATE AND EXCHANGE ON PROFITABILITY IN SHARIA BANKING IN INDONESIA PERIOD OF 2009-2019 - Fuadi, Fuadi; Saparuddin, Saparuddin; Sugianto, Sugianto (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study examined the effect of inflation, BI Rate, and exchange rate on profitability in Islamic banking in Indonesia during 2009-2019. The population and sample in this study were all Islamic banking in Indonesia obtained by purposive sampling technique. This study used quantitative secondary data sourced from financial statements accessed on the official website of Bank Indonesia and the Financial Services Authority. The data analysis method used was Vector Auto-Regressive (VAR) analysis with the help of Eviews 10. The results of the Variance Decomposition (VD) test showed that inflation could affect Return on Assets (ROA) of 0.62%. It indicated that inflation had a low or insignificant effect on the Return On Assets (ROA) of Islamic banking. BI Rate could affect the Return on Assets (ROA) of 0.13%, which indicated that inflation had a low or insignificant effect on the Return On Assets (ROA) of Islamic banking, while the exchange rate could affect the Return on Assets (ROA) of 1.89%, which indicated that the exchange rate had a significant effect on the Return On Assets (ROA) of Islamic banking. Based on the results of this study, it concluded that the exchange rate was more dominant in influencing the Return on Assets (ROA) of Islamic banking in the short and long term.